Biomimetics: Tunable Anisotropic Wettability of Rice Leaf‐Like Wavy Surfaces (Adv. Funct. Mater. 5/2013). (1st February 2013) - Lee, Seung Goo; Lim, Ho Sun; Lee, Dong Yun; Kwak, Donghoon; Cho, Kilwon
<x xml:space="preserve">Abstract</x> Inspired by the hierarchical structures of rice leaf surfaces, synthetic rice leaf‐like wavy surfaces with tunable anisotropic wettability are described by Kilwon Cho and co‐workers on page 547. The nanometer scale roughness of the rice leaf‐like surfaces is controlled to yield tunable anisotropic wettability and hydrophobic properties that transition between the anisotropic/pinned, anisotropic/rollable, and isotropic/rollable water droplet behavior states. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>